2012
DOI: 10.3390/agriculture2040339
|View full text |Cite
|
Sign up to set email alerts
|

The Agricultural Ethics of Biofuels: The Food vs. Fuel Debate

Abstract: Plant-based transportation fuels were the focus of extended criticism in the press, especially during 2008 when a portion of the blame for a spike in global food prices was associated with growth of the United States’ corn ethanol industry. The critique is based on an unsophisticated portrayal of the ethical issues at stake in the food security implications of biofuel. Three ethical critiques can be leveled at the food vs. fuel debate. First, although market drivers of biofuels indeed skew consumptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
88
1
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(93 citation statements)
references
References 22 publications
1
88
1
3
Order By: Relevance
“…See Figure 1). Thompson, 2012a). The actual contribution that biofuels made to the food price hikes has remained contested due to the complexity and uncertainty inherent in attempting to model the different factors at play, although most studies have found that biofuels were a contributing factor (Nuffield Council on Bioethics, 2009; Kretschmer et al, 2012;Zilberman et al, 2012;Zhang et al, 2013;De Gorter et al, 2015).…”
Section: Food Versus Fuelmentioning
confidence: 99%
See 2 more Smart Citations
“…See Figure 1). Thompson, 2012a). The actual contribution that biofuels made to the food price hikes has remained contested due to the complexity and uncertainty inherent in attempting to model the different factors at play, although most studies have found that biofuels were a contributing factor (Nuffield Council on Bioethics, 2009; Kretschmer et al, 2012;Zilberman et al, 2012;Zhang et al, 2013;De Gorter et al, 2015).…”
Section: Food Versus Fuelmentioning
confidence: 99%
“…While the benefits of this simplified framing are clear -it provides a hook on which to hang criticisms of biofuels -we aim to draw attention to the complexities, issues and questions obfuscated by this frame. In this paper, we do not revisit the evidence on the impact of biofuels on food prices (see Kretschmer et al, 2012;Zilberman et al, 2012;Zhang et al, 2013;De Gorter et al, 2015), nor do we examine the moral and ethical arguments concerning biofuels, which have been explored elsewhere (see Thompson 2012aThompson , 2012bGamborg et al, 2012). Nor do we argue for or against biofuels, again a false dichotomy given the diversity of crops, production and processing systems, and political economic contexts in which biofuels are developed and deployed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the proposed alternatives for achieving this is to use green and sustainable alternatives to the conventional feedstock for producing commodity chemicals and fuels. The fuel versus food debate for the 1st generation biofuels led to the development of 2nd generation biofuels where, lignocellulosic biomass (or waste biomass) that does not compete with food crops, is used as the feedstock to produce chemicals and fuels [3][4][5].…”
Section: Biorefineries and Lignin Valorisationmentioning
confidence: 99%
“…We only consider the use of waste biomass in this study. According to the German Advisory Council on the environment, energy crops include several sustainability challenges in agriculture and forestry apart from the discussions on 'food or fuel' [46]. For example, (German) forests serve as a sink for CO 2 .…”
mentioning
confidence: 99%